Multicohort study of change in job strain, poor mental health and incident cardiometabolic disease. Issue 11 (5th September 2019) - Magnusson Hanson, Linda L; Rod, Naja Hulvej; Vahtera, Jussi; Peristera, Paraskevi; Pentti, Jaana; Rugulies, Reiner; Madsen, Ida Elisabeth Huitfeldt; LaMontagne, Anthony D; Milner, Allison; Lange, Theis; Suominen, Sakari; Stenholm, Sari; et al.
Abstract : Objectives: Several recent large-scale studies have indicated a prospective association between job strain and coronary heart disease, stroke and diabetes. Job strain is also associated with poorer mental health, a risk factor for cardiometabolic disease. This study investigates the prospective relationships between change in job strain, poor mental health and cardiometabolic disease, and whether poor mental health is a potential mediator of the relationship between job strain and cardiometabolic disease. Methods: We used data from five cohort studies from Australia, Finland, Sweden and UK, including 47 757 men and women. Data on job strain across two measurements 1–5 years apart (time 1 (T1)–time 2 (T2)) were used to define increase or decrease in job strain. Poor mental health (symptoms in the top 25% of the distribution of the scales) at T2 was considered a potential mediator in relation to incident cardiometabolic disease, including cardiovascular disease and diabetes, following T2 for a mean of 5–18 years. Results: An increase in job strain was associated with poor mental health (HR 1.56, 95% CI 1.38 to 1.76), and a decrease in job strain was associated with lower risk in women (HR 0.70, 95% CI 0.60–0.84). However, no clear association was observed between poor mental health and incident cardiometabolic disease (HR 1.08, 95% CI 0.96–1.23), nor between increase (HR 1.01, 95% CI 0.90–1.14) and decrease (HR 1.08, 95% CI 0.96–1.22) in job strain and cardiometabolic disease. Conclusions: The results did not support that change in job strain is a risk factor for cardiometabolic disease and yielded no support for poor mental health as a mediator.